2023
DOI: 10.2196/40461
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Listening and Digital Profiling Study of People With Headache and Migraine: Retrospective Infodemiology Study

Abstract: Background There is an unmet need for a better understanding and management of headache, particularly migraine, beyond specialist centers, which may be facilitated using digital technology. Objective The objective of this study was to identify where, when, and how people with headache and migraine describe their symptoms and the nonpharmaceutical and medicinal treatments used as indicated on social media. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…In this study, we found that users of X had greater interactions when the content of the tweets was related to headache, likely because headache is the most common neurological disorder in the population 28 . Many studies have demonstrated the use of social media platforms to share experiences with headaches 35,36 . Additionally, there are multiple reports linking headaches with social media use 29 , as somatic symptoms, including headaches, have been found primarily in patients with problematic use of social media 29,37 .…”
Section: Main Findingsmentioning
confidence: 99%
“…In this study, we found that users of X had greater interactions when the content of the tweets was related to headache, likely because headache is the most common neurological disorder in the population 28 . Many studies have demonstrated the use of social media platforms to share experiences with headaches 35,36 . Additionally, there are multiple reports linking headaches with social media use 29 , as somatic symptoms, including headaches, have been found primarily in patients with problematic use of social media 29,37 .…”
Section: Main Findingsmentioning
confidence: 99%
“…Queries from search engines are primarily retrieved by Google Trends [18] , as well as Yandex [19] , Baidu [20] , Bing [21] , and Yahoo [22] . Other notable sources include websites and platforms [23,24] : blogs, YouTube, forums, and online communities. According to Statista, as of July 2023, Google dominated the global search engine market, with a share of approximately 83.49%, compared to Bing (9.19%), Yahoo (2.72%), YANDEX (1.9%), Baidu (0.51%), and DuckDuckGo (0.77%) [25] .…”
Section: Google Trends and Public Interestmentioning
confidence: 99%
“…Only a minor portion of the videos regarding migraine treatment are authorized by healthcare professionals, whereas the majority of the videos are from non-healthcare advisors, which might affect the quality of the treatment received by patients following online platforms [ 8 ]. This might discourage patients from making a hospital visit upon an attack or seeking treatment afterward [ 9 ].…”
Section: Introductionmentioning
confidence: 99%